1990
DOI: 10.1136/jmg.27.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of partial trisomy 7q owing to rare structural rearrangements of chromosome 7.

Abstract: We report, to the best of our knowledge, only the fourth case of trisomy for the interstitial region 7q22-*q31.2 and two cases of trisomy 7q34-*qter, the most distal region yet to be described.Case reports CASE 1 Case 1, born 8.12.87, was the first born of twins to a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 7 publications
(2 reference statements)
0
43
0
Order By: Relevance
“…Four cases of duplicated regions of 7q were large, had complex rearrangements with other chromosomes, and seizures were not a feature (101,102). However, Löffler et al (103) reported siblings with a pure duplication of 7q32-q34, each having a generalized seizure disorder.…”
Section: Other Chromosome 7 Anomaliesmentioning
confidence: 99%
“…Four cases of duplicated regions of 7q were large, had complex rearrangements with other chromosomes, and seizures were not a feature (101,102). However, Löffler et al (103) reported siblings with a pure duplication of 7q32-q34, each having a generalized seizure disorder.…”
Section: Other Chromosome 7 Anomaliesmentioning
confidence: 99%
“…Since the use of banding techniques was introduced in human cytogenetics, at least 41 liveborn patients with well documented partial 7q trisomy have been published: 36 cases previously reviewed by Novales et al [1982], Johnson et al [1986], and Forabosco et al [1988], and five additional cases: one of the two cases published by Zackowsky et al [1990], three cases reported by Romain et al [1990], and one case by Humphreys et al [1991]. In most of them, a terminal partial trisomy was present involving a variety of segments from 7q21→qter to 7q35→qter, whereas in only seven cases, an interstitial partial trisomy involving the segments 7q11.2→q11.23 [Hoo et al, 1982], 7q11→q22 [Kardon et al, 1983], 7q21.12→q31.32 [Humphreys et al, 1991], or 7q22→q31 [Grace et al, 1973;Berger et al, 1974;Serville et al, 1975;Romain et al, 1990] was described.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the reported facial features of monosomy 7q (7q36→qter) [2,4], the special facial appearance of this boy more closely resembled babies with partial trisomy 7q syndrome [9,13]. These babies present with delays in development, feeding difficulty after birth, mental retardation, serious hypotonus, and unusual faces with frontal bossing, macrocrania, widely-set eyes, low nasal features, and low set ears.…”
Section: Discussionmentioning
confidence: 55%